Analisis Faktor-Faktor yang Berhubungan dengan Kinerja Pegawai Dinas Kesehatan Kabupaten Kutai Timur Tahun 2024 - Astuti, Prima Yulia; Adrianto, Ratno; Nurrachmawati, Annisa (Syntax Literate, 2025)
Performance appraisal is a system that is carried out periodically to review and assess individual performance. The Health Department's work results are not yet optimal, as shown by the 12 Minimum Service Standards (SPM) indicators, all SPM indicators have not reached 100% and there are four indicators that have decreased. Discipline is still low, there are often vacancies during effective office hours. The level of employee attendance at morning roll call activities held on Mondays and Thursdays is very low. This research aims to determine the relationship between work discipline, work ability, work motivation, leadership style, work environment and job satisfaction with the performance of East Kutai District Health Office employees. This was a quantitative research with cross sectional design. The population were Health Department employees with civil servant status (95 people), taken using purposive sampling method. Data analysis used logistic regression tests. The research results show that there is a relationship between work discipline (p=0.021), work ability (p=0.000), work motivation (p=0.012), leadership style (p=0.009), work environment (p=0.019) and job satisfaction (p=0.001) with the performance of East Kutai Health Department employees in 2024. The variables work ability, job satisfaction and leadership style are the variables that have the most dominant relationship with the performance of East Kutai Health Department employees in 2024. The East Kutai Health Office needs to improve employee work ability, apply a democratic leadership style, increase employee discipline, implement the best work environment and pay attention to aspects of employee satisfaction by giving awards to employees who excel.